Grandma or Mommy: Familial Labels as Constructs of Identity in Grandfamilies. Issue 4 (2nd October 2019) - Freeman, Jessica D.; Stoldt, Ryan G.
ABSTRACT: One challenge that grandfamilies, families in which grandparents act as caregivers to grandchildren, must navigate is assignment of labels – whether to go by traditional grandparent labels such as "grandma" and "grandpa" or to assume parental labels such as "mom" and "dad." Applying identity theory, this exploratory study investigated how grandfamilies negotiate and apply familial labels as constructs of identity. In-depth interviews ( N = 23) were conducted with grandparents who identified as primary caregiver to at least one grandchild. Thematic analysis revealed three emergent themes and six subthemes: Labeling Strategies (Correction, Submission); Labeling Conflicts (Internal, External); and Identity Duality (Grief, Opportunity).